The Adjunctive Efficacy of Fuzheng Huayu Tablet on Portal Hypertension with HBV Related Cirrhosis: A Protocol for a Multicenter Randomized Controlled Trial - Li Z; Guo Y; Huang J; Lv J; Liu C (Open Access Journal of Clinical Trials, 2025)
Zhengxin Li,1 Yanan Guo,1,2 Jihan Huang,2 Jing Lv,1 Chenghai Liu1,3,4 1Department of Liver Disease, Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, 201203, People’s Republic of China; 2Shanghai University of Traditional Chinese Medicine, Shanghai, 200120, People’s Republic of China; 3Shanghai Key Laboratory of Traditional Chinese Clinical Medicine, Shanghai, 201203, People’s Republic of China; 4Key Laboratory of Liver and Kidney Diseases, Ministry of Education, Shanghai, 201203, People’s Republic of ChinaCorrespondence: Chenghai Liu, Institute of Liver Diseases, Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China, Email chenghailiu@hotmail.com Jing Lv, Department of Liver Disease, Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China, Email ljliver@163.comBackground: Portal hypertension (PH) is a consequence of liver fibrosis and can lead to decompensated cirrhosis with complications such as ascites and gastroesophageal hemorrhage, etc. Liver fibrosis and hepatic architecture disorder contribute to the formation and development of PH. There is an unmet need for curing drugs to improve PH and preventing the occurrence of complications. It is not well known whether anti-liver fibrotic medicines can reduce the risk of PH and decompensated cirrhosis due to HBV, which could be validated by clinical trials.Methods/Design: This is a non-blind, non-placebo-controlled, randomized, multicenter clinical trial. One hundred and ninety-two patients with HBV-related cirrhosis with or without mild gastroesophageal varices in the compensatory stage were enrolled in protocol A. The control group received entecavir (ETV), while the experimental group received Fuzheng Huayu Tablets (FZHY) and ETV. One hundred and eighty-four CHB patients with moderate or severe gastroesophageal varices in the compensatory stage of HBV cirrhosis were enrolled in protocol B. The control group received ETV plus carvedilol (CDL), while the experimental group received FZHY, ETV, and CDL. Both protocols were carried out with 96 weeks of treatment and 12 weeks of follow-up. The primary outcome was the incidence of liver decompensation events in cirrhotic patients. The secondary outcomes included grades of gastroesophageal varices (GEV), liver stiffness measurement, and liver functions. The safety of the testing medicines was also observed.Discussion: Through a multi-center, controlled clinical trial, with the main endpoints of liver decompensated events, we aim to evaluate the clinical efficacy and safety of anti-fibrotic product FZHY on PH in patients with HBV-caused cirrhosis.Trial Registration: Clinical Trials.gov, ID: NCT 02945956/02945982. Registered on Oct 26, 2016.Keywords: portal hypertension, chronic hepatitis B, cirrhosis, decompensation, esophageal varices, Fuzheng Huayu Tablet